Design thinking in the resignification of visagism : Criticism of exclusionary bases and facial measurement - Ritter, Fábio; Brandão, Luciana; Barbosa, Ana Mae; Pereira, Heloisa Mendes (DAT Journal, 2026)
This article investigates the practice of visagism, criticizing exclusionary practices and controversial facial measurement techniques. The objective is to critically review the theoretical bases of visagism, proposing its resignification of praxis through more inclusive approaches, using Design Thinking for this purpose. The methodology of this study is qualitative and descriptive, based on a bibliographic and documentary review, including books, scientific articles, dissertations and theses. When analyzing the origin and evolution of visagism, discussing the dominant cultural influences on concepts of beauty, flaws in the classic visagist approaches, such as facial measurement practices, are identified. In this sense, Design Thinking, as a comprehensive methodology, is proposed as a basis for the consulting process, with the aim of structuring and improving visagist practices. The results indicate that Design Thinking can be an effective tool to make visagism a more inclusive and representative practice, valuing cultural and ethnic diversity.